Contributions of Kartini's thought on women education - Muthoifin; Wachidah, Nur Hanif; Shobron, Sudarno; Ab Rahman, Rozanah (Maya Global Education Society, 2020)
Purpose of the study: The purpose of this paper is to describe Raden Ajeng Kartini’s ideas regarding women’s education, and to analyze the relevance of Raden Ajeng Kartini’s ideas regarding women's education with the development of Islamic education. Methodology: This is library-based research which used a historical and biographical approach by retelling and revealing the history and important events in the life of Kartini. In analyzing the collected data, this paper used content analysis which was described Kartini’s ideas on the women's education that have been manifested and has clear theoretical relevance. Result: Kartini’s idea on education was a critical reaction towards every issue she has faced based on the educational experiences she has received hence emerging as the practical concepts of women’s education. Kartini’s struggle was not merely through ideas but also involved institutional establishment. She was brave enough to take a step forward to established school for women even though it against the Islamic culture. Applications: This research can be used for universities, teaches, and students. Novelty/Originality: The impact on further development was that Kartini’s fight becoming a stimulant for the development of education, specifically in Islamic education which underwent rapid development through the establishment of women’s schools (pesantren) and the advancement of Islamic concepts with the growth of various religious organizations after Kartini.